The Time Value of Money Concept in Islamic Finance (American Journal of Islam and Society, 2006)
The time value of money is a basic investment concept and a basic element in the conventional theory of finance. The Shari`ah does not rule out this consideration, for it does not prohibit any increment in a loan given to cover the price of a commodity in any sale contract to be paid at a future date. What is prohibited, however, is making money’s time value an element of any lending relationship that considers it to have a predetermined value. Here, the Shari`ah requires that a loan be due in the same currency in which it was given. The value (i.e., purchasing power) of paper currencies varies due to changes in many variables over which the two parties of a loan contract usually have no control. This study examines possible modus operandi of time valuation according to the Shari`ah’s precepts vis-à-vis the concept of money, and whether any value can be attributed to time while considering money’s value. For this purpose, it investigates the juristic views on such relevant issues as the permissibility of difference between a commodity’s cash and credit prices and an increase and reduction of the loan’s amount in return for early repayment.